The Role of Intelligence in Mitigating the Covid-19 Pandemic in the South Sumatera Province - Amran, Alfian (Dinasti International Journal of Management Science, 2024)
The problem of this thesis is what the provincial government's policies and the role of intelligence are in dealing with the Covid-19 pandemic in South Sumatra. To analyze the problem, Ryan Nugroho's public policy theory is used, which states that public policy consists of macro, meso and micro policies. Analyzing the role of intelligence using Biddle and Thomas consists of four dimensions, namely the people who take part in social interactions, the behavior that appears in these interactions, position and relationships. Qualitative research methods were used to collect data with sources from the Governor of South Sumatra, Head of the Health Service, Head of BNPB, Regents and Mayors, Hospital Leaders, District Heads and Village Heads, Head of South Sumatra BINDA, KABAGDUKOPS and members of POSDASouth Sumatra Province's policy takes the form of macro policy, namely Law of the Republic of Indonesia number 17 of 2023 concerning health. Government Regulation in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability. South Sumatra province's meso policy in dealing with the Covid-19 pandemic refers to the Republic of Indonesia Minister of Health Regulation number 23 of 2023 concerning guidelines for handling the 2019 corona virus disease (COVID- 19), South Sumatra governor's regulation number 37 of 2020 concerning guidelines for adapting new habits to society productive and safe in the situation of corona virus disease 2019 (COVID-2019) in South Sumatra Province, and micro policies ensure that economic transactions continue to run by implementing health protocols, the Governor of South Sumatra also invites Regents and Mayors to continue to facilitate community activities while adhering to health protocols. The active intelligence role played by KABINDA, KABAGDUKOPS and BINDA SUMSEL in tackling the Covid-19 pandemic, mass vaccination activities and providing mask assistance shows BIN's involvement in supporting the response to the Covid-19 pandemic.